2015
DOI: 10.1371/journal.pone.0128073
|View full text |Cite
|
Sign up to set email alerts
|

Incidence Patterns and Temporal Trends of Invasive Nonmelanotic Vulvar Tumors in Germany 1999-2011. A Population-Based Cancer Registry Analysis

Abstract: ObjectivesTime trends on the incidence and characteristics of invasive vulvar cancer in Germany have so far been studied in few local population- and hospital based tumor registries. We aimed to provide an overview on recent developments of vulvar cancer in Germany, using population-based cancer registry data.MethodsWe analyzed the data on vulvar cancer of eight population-based German cancer registries for the period 1999-2011. ICD-10 codes and ICD-O-3 morphology codes were used to select site and histologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
52
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 22 publications
8
52
0
2
Order By: Relevance
“…This study based on CR data aimed to further investigate a recently reported increase in the incidence of invasive vulvar cancer in Germany [12] by providing stratified incidence trends with regard to age at diagnosis, tumour size and clinical stage, tumour morphology and histopathologic grade over a period of 25 years or longer. Since the beginning of the millennium, the ASR of the incidence of invasive vulvar cancer tripled from 2.5 to 7.9 cases per 100,000 women per year, which almost entirely resulted from additional squamous cell carcinomas and small T1 tumours.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study based on CR data aimed to further investigate a recently reported increase in the incidence of invasive vulvar cancer in Germany [12] by providing stratified incidence trends with regard to age at diagnosis, tumour size and clinical stage, tumour morphology and histopathologic grade over a period of 25 years or longer. Since the beginning of the millennium, the ASR of the incidence of invasive vulvar cancer tripled from 2.5 to 7.9 cases per 100,000 women per year, which almost entirely resulted from additional squamous cell carcinomas and small T1 tumours.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported an increase in vulvar cancer incidence in Germany from approximately two to four new cases per 100,000 women per year between 1999 and 2011 [12]. As some regions with a completeness of case ascertainment of less than 90% had been included in that study [25], it is very likely that the above-cited incidence figures underestimate the true cancer burden.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Western Europe, the average ages are over 70 years (Buttmann-Schweiger et al, 2015). The difference in average ages between Europe and the less developed countries could be explained by the difference in life expectancy at birth.…”
Section: Discussionmentioning
confidence: 99%